Salvation and Inqadh (Deliverance): two theological doctrines in monotheistic religions and their contemporary implication in understanding Islamic penal code - Zein, Ibrahim Mohamed (Asian Christian Review, Kanagawa,Japan, 2008)
Introduction This paper is primarily about the contemporary debate on the implementation of the SharÊÑah. Evidently, the discourse on SharÊÑah in general and Islamic penal code in particular is dominated by issues regarding Islam and modernity, inter-religious dialogue with Christianity and post-colonial state and human rights. The principal issue in such a debate has much less to do with these topics but rather with the fundamental vision of both Islam and Christianity. In addition to that modernity and its sub-discourses on postcolonial state, human rights and others are consequences of the particular history of the Judeo-Christian tradition. Thus, fundamental term such as salvation, which expresses the provision of God for human predicament and redefines the relationship between God and humanity in Christianity in such away that draws the difference between Judaism and Christianity, needs to be studied for a meaningful discourse. Though Islam shares with the Judeo- Christian tradition the story of creation, it has not developed soteriology. Rather it emphasizes “..at birth man stands on the threshold of ethicality, at the zero point of ethical dimension, Islam conceives of his duty as positive deed, as the doing of something new, not as the undoing of something past” . Although al-FÉrËqÊ makes the contrast between falÉh (felicity) and salvation, it is rather essentially the difference between salvation and inqÉdh (deliverance), both of which are acts of God , that is at stake. Indeed felicity presupposes inqÉdh. It is because of inqÉdh the human act will be guided by hidÉyat al-IrshÉd (guidance through the commandments of God). Thus the will of God takes a concrete form in the SharÊÑah. It should be noted that Islam like Judaism does not make any theological claims about Adam’s sin, but rather the QurÑÉn told us that he repented and was forgiven. Much that can be attributed to the story of creation in the QurÑÉn, is that it depicts two patterns of behaviour: Adam’s response to his misdeed and Iblis’ (Satan) attitude of arrogance. Perhaps, the meaning of justice and law can be derived from this story and the story of the two children of Adam. An understanding of the Biblical story of creation within the concept of inqÉdh as in Judaism will mark a sharp distinction between God and humanity. While “salvation” in Christian theology develops a new orientation in the monotheistic vision, inqÉdh retains both the essence of ethics of intent and action and transcendence of God. This paper deals with the contemporary implications of these two moral visions. The focus will be mainly on the legal narratives regarding contemporary codification of Islamic penal code. This is because the penal code is the most problematic and visible in any discourse on the implementation of SharÊÑah. It is equally important that metaphysical postulates of such a debate should be predicated on these two paradigms of salvation and inqÉdh.